Ensino de paleontologia: estratégias para alfabetização científica nos anos iniciais - Boelter, Ruben Alexandre (2024)
Science in the Early Years is of great importance for the formation of a critical student who is aware of the scientific and technological transformations that the world is going through, in this way, Scientific Literacy (CA) is a process in constant construction, in which Teaching needs to be based on a differentiated curriculum that provides a more significant Science Teaching and that later triggers scientific knowledge. In this context, the problem of this research is to investigate how the approach to the theme of Paleontology in the Early Years can contribute to Scientific Literacy? The theoretical framework adopted was the discussion in relation to the Teaching of Science in the Early Years, Curricular Educational Policies, CA, Paleontology, the Teaching of Paleontology and the Didactic Sequence (DS). The methodology is characterized by having a qualitative approach, with a focus on investigation via case study, whose instrument for collecting previous data was organized in a questionnaire that contained a total of 11 questions, two (2) resulting from images classified as open, and nine (9) mixed questions, classified as open and closed, whose purpose was to bring the students' view in relation to Paleontology, developed to 60 students from two (2) classes of the 3rd Year and two (2) classes of the 4th Year of Elementary School, in the participating schools. For data analysis, Content Analysis, proposed by Bardin (2011), was used, through the following stages: pre-analysis; exploration of the material and the treatment of the results; inference and interpretation. As preliminary results, triggered two (2) articles and one (1) manuscript: "The Teaching of Paleontology in the Early Years: exploring the children's imagination through images", "Paleontology, Paleontologists and Fossils: who told me about it?", and "Scientific Literacy from the previous conceptions of students of third and fourth years of Elementary School in relation to Fossils" which led to reflect as a conclusion that children tend to associate paleontology with the discovery and excavations of fossils, and they often lack the understanding of the process and interpretation of the data obtained from the fossils. Also, that they have reductionist or even mistaken conceptions on the subject, such as the idea that all dinosaurs were extinct at the same time, or that fossils are just ancient bones, without making a connection with the formation of fossils. It was also evident that after DS there was an increase in CA indicators, indicating that students are in the CA process, since the situations required them to seek their previous conceptions about Paleontology and assimilate the new scientific concepts that were worked on, interacting and expressing their positions and solutions, strengthening knowledge.